A test of the weak-form of the efficient market hypothesis:evidence using daily data from the Colombo stock exchange - Abeyratna, G.; Power, D.M. (Natural Resources Energy Science Autority of Sri Lanka:Colombo, 1995)
Abstract available from Library, Please quote title when requesting
Keywords: Share price; Economics